If A and B are 2 events, prove that P( A ∩ B ) ≥ 1 - P(A') -P(B') and hence P( A ∩ B ∩ C ) ≥ 1 - P(A') -P(B') - P(C').

thanks! I haven learn about bonferroni inequality..so i dont know how to use it though

Printable View

- Jan 29th 2010, 12:29 PMalexandrabel90simplified prove of bonferroni inequality
If A and B are 2 events, prove that P( A ∩ B ) ≥ 1 - P(A') -P(B') and hence P( A ∩ B ∩ C ) ≥ 1 - P(A') -P(B') - P(C').

thanks! I haven learn about bonferroni inequality..so i dont know how to use it though - Jan 29th 2010, 01:01 PMPlato